Glutamine Improves Innate Immunity and Prevents Bacterial Enteroinvasion During Parenteral Nutrition. (August 2015) - Wang, Xinying; Pierre, Joseph F.; Heneghan, Aaron F.; Busch, Rebecca A.; Kudsk, Kenneth A.
Background : Patients receiving parenteral nutrition (PN) are at increased risk of infectious complications compared with enteral feeding, which is in part explained by impaired mucosal immune function during PN. Adding glutamine (GLN) to PN has improved outcome in some clinical patient groups. Although GLN improves acquired mucosal immunity, its effect on innate mucosal immunity (defensins, mucus, lysozymes) has not been investigated. Methods : Forty-eight hours following venous cannulation, male Institute of Cancer Research mice were randomized to chow (n = 10), PN (n = 12), or PN + GLN (n = 13) for 5 days. Small intestine tissue and luminal fluid were collected for mucin 2 (MUC2), lysozyme, cryptdin 4 analysis, and luminal interleukin (IL)–4, IL-10, and IL-13 level measurement. Tissue was also harvested for ex vivo intestinal segment culture to assess tissue susceptibility to enteroinvasive Escherichia coli. Results : In both luminal and tissue samples, PN reduced MUC2 and lysozyme ( P < .0001, respectively) compared with chow, whereas GLN addition increased MUC2 and lysozyme (luminal, P < .05; tissue, P < .0001, respectively) compared with PN alone. PN significantly suppressed cryptdin 4 expression, while GLN supplementation significantly enhanced expression. IL-4, IL-10, and IL-13 decreased significantly with PN compared with chow, whereas GLN significantly increased these cytokines compared with PN. Functionally, bacterial invasion increased with PN compared with chow ( P < .05), while GLN significantly decreased enteroinvasion to chow levels ( P < .05). Conclusions : GLN-supplemented PN improves innate immunity and resistance to bacterial mucosal invasion lost with PN alone. This work confirms a clinical rationale for providing glutamine for the protection of the intestinal mucosa.